2019
DOI: 10.32497/jobs.v5i1.1671
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Mapping Potensi Ekonomi Makanan Tradisional Sebagai Pangan Fungsional Berbasis Pangan Lokal Kota Surakarta

Abstract: <p><em>This research is based on previous research’s result that there was a image changing of Surakarta City from Batik’s City toward City of traditional Food. There are four objectives of this research, those are; (1) identify Surakarta traditional food’s as functional foods; (2) Mapping the growth of Surakarta’s traditional foods at least five periode; (3) mapping the potential of Surakarta’s traditional foods as a culture heritage’s foods, functional food dan popular foods. (4) mapping the econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
0
0
Order By: Relevance
“…There are also many Sate Kere connoisseurs from the official circle, and they are often ordered as a staple in wedding dishes or formal events at institutions. In line with Sulistyorini et al [52], Sate Kere is a potential traditional food of Surakarta City as a functional food.…”
Section: Sate Keresupporting
confidence: 66%
“…There are also many Sate Kere connoisseurs from the official circle, and they are often ordered as a staple in wedding dishes or formal events at institutions. In line with Sulistyorini et al [52], Sate Kere is a potential traditional food of Surakarta City as a functional food.…”
Section: Sate Keresupporting
confidence: 66%
“…The decreasing of growth rate in Surakarta food sector will be impacted on the Surakarta City's Government Policy to build Surakarta traditional food as an icon or City Branding of Surakarta City. The research result's Sulistyorini et al [2], showed that traditional food such as sate kere, tengkleng, selat Solo, soto rempah, pecel ndeso, nasi liwet, gudeg ceker dan timlo Solo had been popular in Surakarta City, and contributed to the Regional GDP of Surakarta City (72,96%). These 8 Surakarta traditional food could be made as investment driver in Surakarta City.…”
Section: Introductionmentioning
confidence: 99%